2016
DOI: 10.1111/avsc.12290
|View full text |Cite
|
Sign up to set email alerts
|

Compositional changes in thermophilous oak forests in Poland over time: do they correspond to European trends?

Abstract: Questions: Have compositional changes occurred in thermophilous oak forests in Poland during the past two decades? What kinds of drivers might be responsible for these changes? Are the thermophilous oak woods still rich in species or have they rather lost their diversity?Location: Sudetes Mts., SW Poland. Methods:The vegetation of thermophilous oak forests within four distinct areas was surveyed on 92 semi-permanent plots in the time periods from 1992 to 1994 and from 2010 to 2014. The overall pattern in veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…These trends, detected in several studies around Europe (e.g. Hédl, 2004;Bartha, Merolli, Campetella, and Canullo, 2008;Amici et al, 2013;Becker et al, 2017;Reczyńska and Świerkosz, 2017;Perring et al, 2018b) are also consistent with our findings.…”
Section: F I G U R Esupporting
confidence: 94%
“…These trends, detected in several studies around Europe (e.g. Hédl, 2004;Bartha, Merolli, Campetella, and Canullo, 2008;Amici et al, 2013;Becker et al, 2017;Reczyńska and Świerkosz, 2017;Perring et al, 2018b) are also consistent with our findings.…”
Section: F I G U R Esupporting
confidence: 94%
“…Naaf & Kolk, ; Naaf & Wulf, ), forests released from a major disturbance (e.g. fire suppression in McCune & Vellend, ; Li & Waller, ; recent management cessation in Vanhellemont, Baeten, & Verheyen, ; Reczyńska & Świerkosz, ), or forests recently submitted to a new disturbance (e.g. deer browsing in Vild et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The declining species richness of European lowland forests is considered to be a result of the cessation of traditional forest management (Hédl et al., ; Kopecký et al., ) and environmental eutrophication and acidification (Baeten et al., ; Becker, Spanka, Schröder, & Leuschner, ; Jantsch, Fischer, Fischer, & Winter, ). However, changes in species richness are variable and some recent studies actually found increasing species richness in European forests (Förster, Becker, Gerlach, Meesenburg, & Leuschner, ; Reczyńska & Świerkosz, ; Vild et al., ; Strubelt, Diekmann, & Zacharias, ). The species richness of studied sub‐montane forests declined significantly, but the magnitude of these changes was relatively small compared to lowland forests (Bernhardt‐Römermann et al., ).…”
Section: Discussionmentioning
confidence: 99%